PENGARUH PROFESIONALISME, INDEPENDENSI, ETIKA PROFESI, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN, TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI PADANG DAN MEDAN - Mega Rahmi (Imara: JURNAL RISET EKONOMI ISLAM, 2019)
This study aims to determine the effect of professionalism, independence, professionalethics, organizational culture and leadership style of the performance auditor. This type of research isquantitative. The population is all auditors working on a public accounting firm in Padang and Medanincorporated in the Institute of Certified Public Accountants Indonesia totaling 29 public accountingfirm of 98 respondents. Source data used are primary data from questionnaires. Data analysis techniqueusing the measurement model, the structural model and the independent samples t-test. Analysis ofdata using SmartPLS program version 3 and SPSS version 16.The results of this study indicate that theprofessionalism, independence, professional ethics, organizational culture and leadership style affectthe performance of auditors.